Baslawısh klasslarda ingliz tili pánin oqıtıwda zamanagóy pedagogikalıq texnologiyalardan nátiyjeli paydalanıw - Rambergenov, R.G (SCIENCE and SOCIETY, 2024)
The article provides opinions and recommendations on the importance of using pedagogical technologies in teaching English in primary schools of secondary schools.
Keywords: english language; pedagogical technologies; educational process; interactive methods; techniques and methods; competence; innovation; educational content